IMPLEMENTASI PROGRAM WAJIB BELAJAR 12 TAHUN DI PROVINSI DKI JAKARTA (STUDI KOTA ADMINISTRASI JAKARTA TIMUR) - Welly Kusuma Wardani; Puji Astuti; Priyatno Harsasto (Journal of Politic and Government Studies, 2015)
ABSTRACTIONThe numbers of raw participation number (APK) on SMU and SMK in Jakarta Capital City is high, led the Jakarta Provincial Government made a policy to deal with the issue. The policy is 12 years compulsory study program that regulated by Local Regulation (Perda) DKI Jakarta Province No.8 years 2006 about Education System. The City of Administration of East Jakarta is the top of the list among the other City of Administration in Jakarta on SMU and SMK students dropped out number issues by 1.131 students. Therefore in this research, the author will focus on 12 years compulsory study program implementation in the city administration of East Jakarta. The implementation of this program is aimed to increase raw participation number (APK) and reduce school dropout rate in the Capital Jakarta. This research use descriptive of qualitative approach and the data collection method is documentation and interviews. The subject of the research is Jakarta Provincial Education Department, Department of Education Middle East Jakarta City Administration, Section of The School District, and Secondary Education. The analysis of the implementation on this program shows that the success or failure of compulsory study 12 years program in this year really is determined by the organization of implementation and bureaucrat front line. This is due because they have a authority to execute this program and dealing directly with the target group. Apparently the program implementation has good enough achivement based on the structure and tasks of its owned, working mechanism or coordination, human resources, and all financial resources in the organization. But there are several obstacles that still hinder the achievement of the program is the lack of socialize to targets, the fund distribution delays in the beginning every single year, and also a lack of involvement of community organization in this program. The writer suggested that the obstacles that exist for this could be considered and resolved by the Government of Jakarta especially for organizations implementation. Then for the next research could do research on this program in term of overall policy evaluation of the input, the process, and the result. Password : the implementation of policy 12 years study.